The Cold War in Historical and Literary Context: A Sociological Analysis of Socio-Political Conflicts in Patrick Worrall's The Partisan - Amelia Zulftriani; Wajiran Wajiran (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This research examines the Cold War's socio-political conflicts and global impacts as depicted in The Partisan, a historical espionage novel by Patrick Worrall. Using Laurenson and Swingewood's theory of literary sociology, the study explores the novel's portrayal of ideological and military tensions between the United States and the Soviet Union, focusing on the broader implications of these conflicts on modern political, social, and technological systems. Through close textual analysis, the research identifies themes of hegemony, ideological rivalry, and power struggles in the novel, reflecting the Cold War's influence on bloc countries. The study also highlights significant socio-political conflicts, including the arms race, the Berlin Wall crisis, and Baltic resistance, which illustrate the pervasive influence of Cold War ideologies on geopolitical landscapes. The findings underscore the Cold War's role in shaping contemporary societal structures, urban planning, technological advancements, and economic policies. By contextualizing The Partisan within historical events, this research contributes to understanding how literature reflects and critiques the long-term effects of Cold War tensions on global civilization, ultimately revealing the inseparability of historical conflicts from present-day socio-political realities.